Meander cores on the floodplain: the early Holocene development of the low-floodplain along the Lower Tisza Region, Hungary - Kiss, Tímea; Hernesz, Péter; Sipos, György (Journal of Environmental Geography, 2012)
The aim of the present study is to analyse the morphology, sedi-mentary structure and age of flood-free islands on the low-floodplain of the Lower Tisza in order to determine the date and causes of river incision. On the study area the identified 16 elevated surfaces were divided into two groups. The real or meander core floodplain islands appear in the northern and central units of the study area. They are characterized by steep slopes, elevated surface and small territory (2.1 km2 in average). The second type consists of elevated surfaces of point-bar systems and natural levees of paleo-channels, and they mostly appear in the southern unit. They have gentle slopes, smaller relative height and greater area (4.1 km2 in average). The spatial distribution of the two types refers to slow and slight tectonic uplift in the northern part of the study area, though in the south they refer only to the lack of sinking. The results of the sedimentological analysis on the meander core at Szegvár show that it originally belonged to the high-floodplain. Due to the slight tectonic uplift the meandering channel incised into the soft sediments, and as lateral erosion was possible, an ingrown-type meander developed, which later as a result of cut-off has become a meander core (or umlaufberg). Based on the OSL data the incision started at least 20.1±2.1 ka ago, and it terminated ca. 8-9 ka ago. The calculated bankfull discharge of the Szegvár paleo-meander is estimated to be 4000-7500 m3/s, referring to a considerably higher discharge than that of the present-day Tisza (800 m3/s). Similar planimetric meander parameters of paleo-channels on the high and low-floodplain suggest that the incision was not driven by climate, i.e. discharge change but primarily by tectonic movement. This is also supported by the height condition of the islands, as their surface is almost at the level of the high-floodplain.